Corporate Social Responsibility: The critical analysis of its understanding and applicability by small scale mining companies in Tanzania: A case study of Geita District - Rubanzibwa, Doris (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University in partial fulfilment of the requirements for award of the degree of Masters of Business Administration in Corporate Management(MBA-CM) of Mzumbe University